2014
DOI: 10.3389/fncir.2014.00040
|View full text |Cite
|
Sign up to set email alerts
|

Origin and neurochemical properties of bulbospinal neurons projecting to the rat lumbar spinal cord via the medial longitudinal fasciculus and caudal ventrolateral medulla

Abstract: Bulbospinal systems (BS) originate from various regions of the brainstem and influence spinal neurons by classical synaptic and modulatory mechanisms. Our aim was to determine the brainstem locations of cells of origin of BS pathways passing through the medial longitudinal fasciculus (MLF) and the caudal ventrolateral medulla (CVLM). We also examined the transmitter content of spinal terminations of the CVLM pathway. Six adult rats received Fluorogold (FG) injections to the right intermediate gray matter of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Two pathways known to have a powerful influence on motor networks are the corticospinal tract (CST) and the reticulospinal tract (RST) [ 1 ]. In the rat the CST projects directly from the sensorimotor cortex and terminates principally in the deep dorsal horn and intermediate grey matter [ 3 5 ] whereas the RST originates from medullary and pontine nuclei [ 6 9 ] and terminates principally within the intermediate grey matter and lamina (VIII) [ 5 , 10 , 11 ]. Components of this pathway are monosynaptically activated by corticobulbar pathways and form an indirect cortico-reticular pathway to the spinal cord [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two pathways known to have a powerful influence on motor networks are the corticospinal tract (CST) and the reticulospinal tract (RST) [ 1 ]. In the rat the CST projects directly from the sensorimotor cortex and terminates principally in the deep dorsal horn and intermediate grey matter [ 3 5 ] whereas the RST originates from medullary and pontine nuclei [ 6 9 ] and terminates principally within the intermediate grey matter and lamina (VIII) [ 5 , 10 , 11 ]. Components of this pathway are monosynaptically activated by corticobulbar pathways and form an indirect cortico-reticular pathway to the spinal cord [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al () also distinguish the PnV (ventral pontine reticular nucleus), containing a minor population of reticulospinal neurons, which may in fact be the most rostral part of the medullary gigantocellular nucleus, potentially misconstrued as having a pontine location because of mismatch between coronal sections of the adult brain and the planes of rhombomere boundaries (see below). With regard to laterality, Basbaum and Fields (), Auclair et al (), Vanderhorst and Ulfhake (), and Huma et al () all report an ipsilateral predominance in the projection of pRS neurons throughout the PRF, including both the PnO and the PnC. Newman () concurs, with a distinction between the PnC (his RPoC) pars alpha and beta, which project, respectively, with contralateral and ipsilateral predominance, and between the PnO (his RPoO) medialis and lateralis, which project, respectively, with a weak ipsilateral predominance and no lateral bias.…”
Section: Discussionmentioning
confidence: 92%
“…Several previous retrograde tracing studies have demonstrated projections from the PRF to the spinal cord in the mouse and rat, ranging from embryonic to adult stages (mouse: Auclair et al, ; Vanderhorst and Ulfhake, ; Liang et al, ; rat: Basbaum and Fields, ; Satoh, ; Watkins et al, , 1981; Leong et al, ; Newman, ; Jones and Yang, ; Nudo and Masterton, ; Rye et al, ; Shen et al, ; Masson et al, ; Lakke, ; Auclair et al, ; Reiner et al, ; Huma et al, ). Only three of these studies combined unilateral tracer application with contralateral spinal cord hemisection to ensure unilateral tracing so that the laterality of projections could be unequivocally documented (Basbaum and Fields, ; Auclair et al, ; Vanderhorst and Ulfhake, ), as we have done here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations